Constituents from the Root of Lantana camara - A. Al-Fadhli1, Ammar; A. Nasser2, Jamal (Asian Journal of Chemistry, 2014)
Four known secondary metabolites, namely 11b,23S,24R,25-tetrahydroxyprotost-13(17)-en-3- one(alisol A-1), lantanilic acid (2), 3b-hydroxystigmast-5-en-7-one(3) and sitosterol (4), were isolated from the roots of Lantana camara. The structures of these compounds were established by usual spectroscopic methods. This is the first report of alisol A from Lantana camara roots.